New design for intelligent parking system using the principles of management information system and image detection system - Yass, A.A.; Yasin, N.M.; Zaidan, B.B.; Zaidan, A.A. (2009)
Management Information System (MIS) is the design and management of IT (Information Technology) for an organization. It focuses on the best way to enable the organization to meet its goals and business challenges. In this paper we review the techniques used in parking systems. In particular we describe how the principles of MIS is used o improve the system used in car park environment; thus proposing a new design for intelligent parking system to overcome the current parking problems. This paper focuses on the Malaysian parking system as the research case study. Image processing is involved in the texture analysis. It is important to quantitatively evaluate differences of system used using texture features. This paper also discusses how image detection system is used to improve the parking system.